Transient HDO rovibrational satellite peaks in solid parahydrogen: evidence of hydrogen atoms or vacancies? - Wonderly, William R.; Anderson, David T. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
We present FTIR studies of the 193 nm photolysis of fully deuterated formic acid (DCOOD) isolated in solidparahydrogen at 1.9 K which show evidence of transient HDO rovibrational satellite peaks. The S1 and S2 satellitepeaks are readily detected for a-type (101 ← 000) rovibrational transitions of HDO either during or immediately after photolysis. Intensity measurements show the HDO b-type (111 ← 000) rovibrational transitions havesatellite peaks as well, but due to the greater linewidth of these absorptions, the satellite peaks cannot be spectroscopically resolved from the monomer transition and are therefore difficult to detect. These newly identified HDO satellite peaks may result from the HDO photoproduct being formed next to an H atom or a vacancy in the parahydrogen solid. The development of the infrared spectroscopy of these satellite peaks can provide a new means to study radiation effects on low-temperature hydrogen solids doped with chemical species.